Spatial variation in avian bill size is associated with humidity in summer among Australian passerines. Issue 1 (December 2016) - Gardner, Janet; Symonds, Matthew; Joseph, Leo; Ikin, Karen; Stein, John; Kruuk, Loeske
Abstract Background Climate imposes multiple selection pressures on animal morphology. Allen's Rule proposes that geographic variation in the appendage size of endotherms, relative to body size, is linked to climatic variation, thereby facilitating heat exchange and body temperature regulation. Thus relatively larger appendages tend to be found in animals in warmer climates. Despite growing understanding of the role of the avian bill as an organ for heat exchange, few studies have tested the ecological significance of bill size for heat dissipation across species and environmental gradients. Amongst those that have, most have focused on the relationship with ambient temperature, but there is growing evidence that humidity also has a strong influence on heat dissipation. In particular, increasing humidity reduces the potential for evaporative cooling, favouring radiative and convective heat loss via the bill, and hence potentially favouring larger bills in humid environments. Here, we used phylogenetically-controlled analyses of the bill morphology of 36 species of Australian passerines to explore the relationship between bill size and multiple aspects of climate. Results Humidity during the hot summer months (December-February) was positively associated with relative bill surface area across species. There was no overall association between bill size and summer temperatures per se, but the association with humidity was mediated by temperature, with a significant interaction indicating stronger associations with humidity at cooler summer temperatures. This is consistent with the idea that larger bills may become disadvantageous in humid conditions as ambient temperature approaches body temperature. Relative bill size was similar among closely related species, with phylogeny explaining 63.3% of the variance, and there was significant variation among species in their response to humidity. However, the relationship between relative bill size and humidity was not associated with phylogeny. Conclusions Our results are consistent with the idea that body temperature regulation underlies continent-wide patterns of bill size variation in a broad range of Australian passerines, and suggests that Allen's Rule may apply to humidity gradients as well as temperature gradients. They add to growing evidence that a narrow focus on temperature alone in studies of responses to climate change may limit our understanding of species' sensitivities to climatic variation, and of their capacity to adapt.